Smart Grid technology. Prospects for the development of electric networks - Tolegenova Г.Б.; Zakirova А.Б.; Zhmud В.А.; Kalimoldaev М.Н. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
In parallel with the development of technology, the need for electricity is rapidly increasing, and not only production, but also energy distribution is becoming an important issue. Consequently, the progressive demand for reliability, productivity, safety, environmental friendliness and energy stability is piling up the circuits of electrical networks. They are creating an intelligent energy system, which is now commonly known as the concept of "smart grids". This article presents an overview of «Smart Grids» with their features and various aspects in the field of electricity distribution. Intelligent electrical networks and their development are considered. In addition, this article is devoted to the analysis of intelligent electrical networks, the advantages of their introduction into the daily lives of consumers. The prospects of the stages of development of «Smart grids» in most countries of the world were considered, as well as some foreign projects aimed at improving energy efficiency and the functioning of smart electric networks.